Study of the correlation of epicardial adipose tissue with left ventricular mass and left ventricular mass index in patients with essential hypertension - Goswami, Sourabh; Keswani, Prakash; Chaturvedi, Neeraj; Sharma, Shrikant; Sharma, Ramji (International Journal of Research in Medical Sciences, 2020)
Background: Epicardial Adipose Tissue (EAT) is recognized to be a cardiovascular risk factor. In addition to providing fuel to heart, it plays a pivotal role in the pathogenesis of atherosclerosis though the secretion of adipokines. This study aims to find the correlation of EAT with Left Ventricular Mass (LVM) and Left Ventricular Mass Index (LVMI) in patients with essential hypertension. Increasing LVM and LVMI are predictors of poor cardiovascular outcome. So, if we find a positive correlation, we can say that measurement of epicardial fat in essential hypertension may help us identify high risk hypertensive patients. Methods: This study was carried out in SMS Hospital, Jaipur, after approval from the Ethics Committee. 100 consecutive eligible patients were included in the study after application of inclusion and exclusion criteria and taking proper informed consent. After history, examination and routine laboratory investigations, all patients underwent transthoracic 2D and Doppler echocardiography. EAT thickness, LVM and LVMI were measured and correlated using Spearman correlation coefficient. Results: The mean LVM was 139±42.12 g and mean LVMI was 35.76±11.28 g/m2.7. The spearman correlation coefficient (r) was calculated to be 0.691 between EAT and LVM and 0.677 between EAT and LVMI, indicating strong positive correlation between EAT and both LVM and LVMI. This implies that as; EAT increases, LVM and LVMI increases significantly. Conclusions: Thus, authors have found that EAT is positively correlated with LVM and LVMI. So, we can say that increase in EAT may lead to adverse cardiovascular outcome in patients with essential hypertension.